Avaliação do comportamento biológico de diferentes tratamentos de superfície de implantes cerâmicos de zircônia : revisão sistemática - Zingano, Cristiano Aguiar (2022)
Introduction: In dentistry, titanium implants are used for many decades and are considered the gold standard of biomaterial. However, reserved on the aesthetic issue. To minimize this problem, zirconia was proposed as a substituted biomaterial. In order to improve the biological properties, both titanium and zirconia surfaces are modified. The aim of this article is to carry out a systematic review of the literature to answer whether surface treatments performed on zirconia can generate different cellular and/or bacterial biological responses compared to textured titanium surfaces. Materials and methods: A literature review was carried out based on the recomendations proposed in the PRISMA guide and was registered at PROSPERO database (CRD 4202123384). The literature search took place in the main electronic databases, PUBMED/MEDLINE, EMBASE, LILACS, COCHRANE LIBRARY and EBSCO using the selected keywords, in a period of 10 years, only articles in Portuguese, English and Spanish were used. The articles found were selected according to inclusion and exclusion criteria by two researchers in two phases and, after reading, data were extracted. Results: During the search 9302 articles were found. From these 51 articles were selected after the first phase selection and 13 remained after de second phase. Of the articles selected to enter the review, 9 articles tested in vitro properties of cellular behavior on the various Zirconia surfaces, 3 articles tested in vitro the bacterial presence and in only 1 article there were both tests. Conclusion: The results of the reviewed articles suggest that zirconia-treated surfaces present better biological results in terms of cell adhesion and migration, as well as bacterial adhesion in vitro compared to titanium-treated surfaces.